Management of failed periodontal surgical intervention for a furcal lesion with a nonsurgical endodontic approach - Saeed Asgary; Mahta Fazlyab (Restorative Dentistry & Endodontics, 2014)
As long as the prognosis of teeth remains a matter of concern, the endodontic-periodontal relationship will be considered a challenge for the clinician. Many etiologic factors, including bacteria, fungi, and viruses, plus other contributing factors, such as trauma, root resorptions/perforations, and dental malformations, play a role in the co-occurrence of endodontic and periodontal lesions. Whatever the cause, a correct diagnosis on which to base the treatment plan is the key to successful maintenance of the tooth. This article reports the successful endodontic management of a furcation lesion in a mandibular molar that was nonresponsive to a previous periodontal surgical graft. The case had presented a diagnostic challenge for the clinicians, and this article reviews the key points that can lead to a correct diagnosis and treatment planning.